2022
DOI: 10.14202/vetworld.2022.2953-2961
|View full text |Cite
|
Sign up to set email alerts
|

Nationally and locally-initiated One Health approach in controlling rabies in West Kalimantan, Indonesia

Abstract: Background and Aim: Rabies is one of the prioritized zoonoses in Indonesia and West Kalimantan is one of the rabies-endemic provinces in the country. This study aimed to evaluate a locally-initiated One Health approach to implement rabies prevention and control programs in Pontianak City and Sanggau District (through a bottom-up approach), and the central government initiated a program in Ketapang District (through a top-down approach). Materials and Methods: Data were collected using three focused group disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Wild and domestic animals are reservoirs for zoonotic pathogens in Indonesia [62,63]. The wildlife trade and habitat destruction contribute to the spread of pathogens from wildlife to humans, leading to outbreaks of diseases such as rabies and leptospirosis [64][65][66]. Additionally, close contact with livestock, poultry, and companion animals increases the risk of zoonotic transmission.…”
Section: Overview Of Zoonotic Diseases In Indonesiamentioning
confidence: 99%
“…Wild and domestic animals are reservoirs for zoonotic pathogens in Indonesia [62,63]. The wildlife trade and habitat destruction contribute to the spread of pathogens from wildlife to humans, leading to outbreaks of diseases such as rabies and leptospirosis [64][65][66]. Additionally, close contact with livestock, poultry, and companion animals increases the risk of zoonotic transmission.…”
Section: Overview Of Zoonotic Diseases In Indonesiamentioning
confidence: 99%
“…Of the many interventions in the progress and awards received by the City of Pontianak, one of the professions that also contributed was civil servants (PNS) Aptriana et al (2022). Civil servants are people employed by government agencies to provide public services, and are still considered a very popular profession (Schuster et al, 2020;Mazzucato & Kattel, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another priority zoonotic disease is rabies, which is endemic in 26 of 34 provinces in Indonesia and causes 99% mortality in animals and humans [ 17 ]. In recent months, rabies cases have experienced a spike in Indonesia, such as Bali, Kalimantan, and Sulawesi, resulting in death within just <48 hours after being bitten [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can also be seen from the various studies we analyzed using bibliometric analysis. We found that the research focus related to One Health, especially in Indonesia, is minimal (32 articles) from 2016 to 2022 and has shifted, primarily focusing on the latest issues, so that the topic of One Health is only associated with and not employing One Health as the research foundation [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation